Penurunan Skala Nyeri Dismenore Primer pada Remaja Putri Menggunakan Masase Effleurage - Muhammad Amin; Yesi Purnamasari (Journal of Telenursing (JOTING), 2020)
This study aimed to determine the scale of pain before and after being given effleurage massage therapy for adolescent girls experiencing primary dysmenorrhea. The research method used in this study is a pre-experimental method with a pretest-postest design. The results showed that the p-value before and after being given effleurage massage therapy was 0.000 (<0.05). In conclusion, there is an effect of effleurage massage therapy on reducing the pain scale of primary dysmenorrhea in young women at SMP Muhammadiyah Terpadu, Bengkulu City. Keywords: Primary Dysmenorrhea, Effleurage Massage, Pain Scale